Kite String or Manja Cut Injury: A New Culprit - Surendrakumar B. Patil; Neha Gupta; Anshoo Gandhi; Mayank Bhasin; Prabhakar Rakhonde; Sushil Machhale (Indian Journal of Plastic Surgery)
Background Kite string injuries (manja cut injuries), particularly those caused by Chinese manja, are new culprit of emergencies especially in the month of January in Maharashtra region. These injuries commonly affect the neck, face, hands, and legs, especially among individuals traveling on two wheelers. The visibility challenge, where the kite's thread is difficult to see, further exacerbates the risk.